The Effect Of Good Corporate Governance On Profit Management In Manufacturing Companies Listed On The Idx Period 2020–2022 - Abdul Syukur; Abdul Karim; Asrianto Asrianto (Jurnal Mirai Management, 2023)
The purpose of this study is to examine the impact of business governance on the wage system. The independent changes used in this study are the board of commissioners, audit committee, and institutional authorities. In this study, the size of the commission board is measured by including all members of the commission board in the company. The research committee in this study was evaluated based on the number of corporate book committee members. In addition, the ownership structure of a company is estimated by the percentage of the number of shares owned by the entity from the total residual component. Revenue management is presented as a type of cash-based option for Jones. This research was written using data from www.idx.co.id. This research uses examples of the manufacturing sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The results of this study also show that the membership of the board of commissioners, audit committees, and institutions has a significant influence on revenue management. However, only the Audit committee influences revenue management. Keywords: GCG; Profit management; Manufacturing company; IDX.